The dopamine transporter gene may not contribute to susceptibility and the specific personality traits of amphetamine dependence. (1st April 2015) - Tzeng, Nian-Sheng; Lu, Ru-Band; Yeh, Hui-Wen; Yeh, Yi-Wei; Huang, Chang-Chih; Yen, Che-Hung; Kuo, Shin-Chang; Chen, Chun-Yen; Chang, Hsin-An; Ho, Pei-Shen; Cheng, Serena; Shih, Mei-Chen; et al.
Highlights: DAT1 gene was analyzed in patients with amphetamine dependence (AD), and different personality. A weak association was found between the rs27072 polymorphism and development of AD. The borderline associations were not evident in subsequent correction. High harm avoidance and novelty seeking personality may be a risk factor for the development of AD. DAT1 gene may not contribute to AD susceptibility and specific personality traits. Abstract: Background: A substantial amount of evidence suggests that dysfunction of the dopamine transporter may be involved in the pathophysiology of amphetamine dependence (AD). The aim of this study was to examine whether the dopamine transporter gene ( DAT1, SLC6A3 ) is associated with development of AD and whether this gene influences personality traits in patients with AD. Methods: Eighteen polymorphisms of the DAT1 gene were analyzed in a case-control study that included 909 Han Chinese men (568 patients with AD and 341 control subjects). The patients fulfilled the DSM-IV-TR criteria for AD. The Tridimensional Personality Questionnaire (TPQ) was used to assess personality traits and to examine the association between these traits and DAT1 gene variants. Results: A weak association was found between the rs27072 polymorphism and development of AD, but these borderline associations were unconfirmed by logistic regression and haplotype analysis. Although harm avoidance and novelty seeking scores were significantly higher in patients than in controls, DAT1 polymorphisms did not influence these scores. Conclusions: This study suggests that high harm avoidance and novelty seeking personality traits may be a risk factor for the development of AD. However, the DAT1 gene may not contribute to AD susceptibility and specific personality traits observed in AD among Han Chinese men.